Knowledge, awareness, and perception on root canal treatment among South Indian population - A survey - C Pratheebha; R Gayathri; Vishnu Priya Veeraraghava; S Kavitha (Wolters Kluwer Medknow Publications, 2022)
The pulp is removed, and the interior of the tooth is cleaned and sealed during root canal treatment. Root canals are dreaded by many people because they are considered to be painful. The following are indicators of pulpal damage, color changes, swelling, thermal sensitivity, and pain in the gums. The pulp gets inflamed or diseased when it becomes infected, then RCT or extraction is needed to eliminate the inflamed or infected tissue and heal that particular region. The questionnaire was circulated to the sample population through a Google Docs link. Pie charts with a frequency table were created when the survey data were acquired. The Chi-square test was used to evaluate the connection using the SPSS software. Eighty-four percent of people are aware of RCT and what it is intended for and 80% of the participants themselves have undergone endodontic treatment. Most of the South Indian population were aware of root canal treatment and have undergone an RCT procedure.